Reducing Labor Pain Intensity within First Stage Active Phase through Hegu LI 4 Acupressure and Quranic Recital Method - Nurul Azizah; Rafhani Rosyidah; Hanik Mahfudloh (Jurnal Ners, 2020)
Introduction: Labor pain is one of the greatest pains experienced by a woman in their life. The purpose of this study was to examine the effectiveness of acupressure and Quranic recital on labor pain reduction.Methods: The study design uses quasi-experiment with comparison between pretest and posttest on non-equivalent control group. Samples were as many as 30 laboring mothers in each group, totaling 60 samples who had been chosen through consecutive sampling technique. The labor pain was assessed through the NRS (Numeric Rating Scale) then analyzed univariately with mean and standard deviation, followed by independent T-sample statistical test such as bivariate analysis.Results: The average pain reduction score in the Hegu LI 4 acupressure group was higher than the Quranic recital of Surah Ar-Rahman group. The acupressure group average pain reduction was 3.03 ± 0.718 while the Quranic recital group was 2.57 ± 1.006. The difference in the average score of independent T-test was significant with the P < 0.007 and 95% C.I. -0.919-( -0.015)Conclusion: Hegu LI 4 acupressure and Quranic recital of Surah Ar-Rahman treatments were promising and may be utilized to reduce labor pain intensity within labor’s first stage active phase. Hegu LI 4 acupressure group   had a greater reduction in labor pain intensity than the Quranic recital of Surah Ar-Rahman group. This study suggests that Hegu LI 4 can be utilized to reduce labor pain as a non-pharmacological therapy.